Seroprevalence of Anti-Rubella IgG Antibodies Among Women of Chilbearing Age: A Croos-Sectional Study - G, Sruthi; Rashmi; Soumya GS (Gayaku Publisher, 2024)
Rubella infection, while typically mild and self-limiting in adults, poses significant teratogenic risks during pregnancy, potentially leading to Congenital Rubella Syndrome (CRS) with a 75-100% transmission rate during the first trimester. This study aimed to assess the need for adult vaccination by detecting anti-rubella IgG titers in women of childbearing age and examining the correlation between vaccination history and seroprevalence. A total of 130 women, including 35 pregnant women, were tested for anti-rubella IgG antibodies using Enzyme-Linked Immunosorbent Assay. Results showed that 102 women (78.47%) were seropositive while 28 (21.53%) were seronegative. Among those with complete vaccination history, 60 women (46.15%) were seropositive, while 6 were seronegative. Of those with unknown vaccination status, 42 women (32.30%) were seropositive and 7 were seronegative. All unvaccinated women were seronegative. In the pregnant women subgroup, 32 were seropositive while 3 showed seronegativity. The finding that 21.53% of women were seronegative, including some with vaccination history, highlights a significant population at risk for rubella infection during pregnancy. This study underscores the importance of evaluating rubella susceptibility in women of reproductive age and suggests the need for considering adult and adolescent vaccination strategies to prevent CRS, even in regions where rubella vaccination is included in the national immunization schedule.